Perancangan Pengelolaan Stok Barang Berbasis Web Dengan Metode Prototype Pada Toko Hosana Salatiga - Wicaksono, Damar Cahyo Setyo; Rudianto, Christ (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Hosana Store Salatiga is a store that sells various office stationery, photocopy and manymore. Hosana Store has many problems, including note recording and inventory management. This is because the business process at Hosana Store is still conventional. Therefore, this research aims to design a web-based information system to assist in data management and note recording. This research utilizes a qualitative method with the assistance of Figma to create designs using a prototype approach. With this design, a web-based information system will be developed to help with data management and note recording at Hosana Store Salatiga, preventing errors in its management.